Sodium ferromanganese pyrophosphate positive electrode material as well as preparation method and application thereof

By doping potassium, magnesium and chlorine into the positive electrode material of ferromanganese pyrophosphate and covering the conductive polymer layer on its surface, the problems of poor conductivity and poor circulation performance of the material are solved, and its performance and stability in high energy density applications are significantly improved.

CN119786572APending Publication Date: 2025-04-08HUNAN XIANNA TECH CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411983029.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The poor conductivity and circulation performance of the cathode material of ferromanium manganese phosphate pyrophosphate have resulted in insufficient competitiveness in high energy density applications.

Method used

Potassium, magnesium and chlorine are doped at the sodium, iron and oxygen positions of sodium manganese phosphate pyrophosphate and coated with conductive polymer layers on the surface of the material, a polymer cladding layer is formed to improve conductivity and cycling stability.

Benefits of technology

Improves the conductivity and cyclic stability of the cathode material, enhances its performance in high-rate discharge and high energy density applications, and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005221947090000131
    Figure BDA0005221947090000131
Patent Text Reader

Abstract

The invention discloses a sodium ferromanganese pyrophosphate positive electrode material as well as a preparation method and application thereof. The sodium ferromanganese pyrophosphate positive electrode material comprises a positive electrode base material and a polymer coating layer coating a part of surface or the whole surface of the positive electrode base material, the positive electrode base material comprises Na (4-x) KxFe (3-y-z) MnyMgz (PO4) 2P2O7Clf, x is more than or equal to 0 and less than 0.05, y is more than or equal to 0 and less than 2.2, z is more than 0.01 and less than 0.05, and f is more than or equal to 0 and less than 0.03; and the polymer coating layer is prepared from the following raw materials: a conductive polymer and iodine. The invention provides a sodium ferromanganese pyrophosphate positive electrode material as well as a preparation method and application thereof, and solves the technical problems of poor conductivity and poor cycle performance of a material in the prior art.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a sodium manganese iron pyrophosphate positive electrode material and a preparation method and application thereof. Background Art

[0002] Sodium ion batteries have attracted widespread attention in recent years due to their abundant sodium resources, low cost, high safety performance and good low-temperature performance. They have become one of the important energy storage technologies after lithium ion batteries. The positive electrode material of sodium ion batteries is one of the key factors that determine their battery performance. 4 Fe 3 (PO 4 ) 2 P 2 O 7 ] has become a potential cathode material for sodium ion batteries due to its excellent safety and low cost. However, the low voltage platform of sodium iron pyrophosphate limits its energy density, which in turn affects its competitiveness in high energy density applications. To solve this problem, researchers proposed to dope the sodium iron ion (Mn) with cheap manganese ions. 2+ ) to increase the voltage platform of the material, thereby enhancing its energy density and expanding its scope of application. However, the doping of manganese ions will bring a series of negative effects. First, the incorporation of manganese ions may lead to a decrease in the electrical conductivity of the material, thereby affecting the full utilization of its capacity. Secondly, manganese ions are affected by the Jahn-Teller effect and are prone to dissolution during the charge and discharge process, resulting in the collapse of the crystal structure and ultimately reducing the cycle stability of the material. In existing studies, the solid phase sintering method is used to prepare sodium manganese iron pyrophosphate, but no effective solution to the Jahn-Teller effect caused by manganese ions and the poor cycle performance of the material is proposed. There are also studies on the preparation of gradient distributed manganese ions and iron ions by coprecipitation, in order to improve the cycle stability of the material. However, this method is complicated to operate, it is difficult to achieve an ideal and uniform distribution of manganese ions, and the technical difficulty in the preparation process is relatively large, and it is difficult to meet the requirements of large-scale production.

[0003] Therefore, how to effectively improve the cycle performance of sodium ferromanganese pyrophosphate is still a technical problem that needs to be solved urgently. Summary of the invention

[0004] The present invention aims to solve the above technical problems existing in the prior art. To this end, the present invention proposes a sodium manganese iron pyrophosphate positive electrode material and a preparation method and application thereof to solve the technical problems of poor electrical conductivity and poor cycle performance of the material in the prior art.

[0005] The invention also provides a method for preparing the positive electrode material.

[0006] The present invention also provides a positive electrode sheet, and the raw materials for preparing the positive electrode sheet include the positive electrode material.

[0007] According to one aspect of the present invention, a positive electrode material is provided, comprising a positive electrode base material, and a polymer coating layer coated on a part of or the entire surface of the positive electrode base material;

[0008] The positive electrode matrix material includes Na 4-x K x Fe 3-y-z Mn y Mg z (PO 4 ) 2 P 2 O 7 Cl f , where (0≤x<0.05, 0≤y<2.2, 0.01<z<0.05, 0≤f<0.03);

[0009] The raw materials for preparing the polymer coating layer include: conductive polymer and iodine.

[0010] According to the first aspect of the present invention, there are at least the following beneficial effects:

[0011] The positive electrode material provided by the present invention includes sodium manganese iron pyrophosphate, and potassium is doped at the sodium position of the sodium manganese iron pyrophosphate, magnesium is doped at the iron position, and chlorine is doped at the oxygen position. Wherein, the sodium position, iron position and oxygen position of the sodium manganese iron pyrophosphate all have corresponding doping elements potassium, magnesium and chlorine, and the atomic radius of the potassium element is larger than the atomic radius of the sodium element. The doping of the potassium element expands the running channel for the sodium element, and the doping of the magnesium element improves the conductivity of the positive electrode material, inhibits the Na-Fe anti-site defect, stabilizes the crystal structure, and increases the diffusion rate of sodium ions. By doping the three elements simultaneously and controlling the doping amounts of the sodium position, iron position and oxygen position, the three-position doping plays a synergistic role, so that the unit cell volume of the modified positive electrode material after doping is reduced, and the sodium ion (Na + ) diffusion resistance, and the Na-O bond is elongated, the Fe-O, PO bonds are shortened, the Na-O bond interaction is weakened, and it is easier to break, reducing the Na + The deintercalation resistance of Na + The diffusion rate is beneficial to the capacity of the modified cathode material, and the synergistic effect inhibits the Mn 2+ The Jahn-Teller effect stabilizes the lattice structure and improves the high-rate discharge performance.

[0012] The polymer coating layer provided by the present invention is that after the conductive polymer is doped with iodine, i.e., P-type doping, the polymer main chain loses electrons and undergoes oxidation, resulting in additional holes, and the localized π electrons of the polymer are excited and easily migrate on the molecular chain, thereby improving the conductive performance of the conductive polymer. The conductivity before and after doping increases from about 100 s / cm to 600 s / cm-1700 s / cm.

[0013] In some embodiments of the present invention, the conductive polymer includes at least one of polypyrrole, polythiophene, polyaniline and polyacetylene.

[0014] The above conductive polymers all have high electronic conductivity and can provide a fast transmission channel for current. During the operation of the sodium ion battery, the conductive polymer forms a conductive network and forms a good conductive connection with the positive electrode material of the sodium ion battery, reducing the transmission resistance of electrons in the material. Especially during high-rate discharge, the conductive polymer can effectively improve the high-rate discharge capacity and stability of the battery. On the other hand, the above conductive polymer has a certain flexibility and can be effectively coated on the surface of the sodium iron manganese pyrophosphate material to form a protective layer, which can slow down the structural damage caused by volume expansion and contraction of the material during the charge and discharge process, especially to prevent the agglomeration and shedding of particles during the cycle process, thereby improving the long-term cycle stability of the material. On the other hand, the nanostructure and high surface area of ​​the conductive polymer help to establish more sodium ion diffusion channels in the material, especially during high-rate charge and discharge, the presence of the polymer helps to reduce the diffusion resistance of sodium ions in the material, and the synergistic sodium iron manganese pyrophosphate material can further optimize the ion conduction characteristics and improve the overall battery charge and discharge efficiency. Specifically, the doping of potassium can not only change the structure of the material, but also significantly expand the diffusion channel of sodium ions. The radius of the potassium ion (approximately ) than sodium ions (approximately ) is large, which enables potassium doping to increase the porosity in the lattice, thereby providing more diffusion paths for sodium ions. Polythiophene forms a thin film on the surface of the potassium-doped material, which helps to maintain the structural stability of the electrode. At the same time, the flexibility of polythiophene enables the material to withstand large volume changes during the charge and discharge process, reducing the collapse or blockage of the sodium ion diffusion channel. The amino groups of polyaniline may react with metal ions (such as Mn) during the charge and discharge process. 2+ , Fe 3+) complexation, reducing the dissolution and precipitation of metal ions in the battery, improving the cycle stability of the material, and can interact with ions in the electrolyte through electrochemical reactions to help the material distribute the charge more evenly, improve the efficiency of the battery, and reduce the cracking or peeling problems caused by volume changes in magnesium-doped materials. Polyacetylene itself has high conductivity and can form a good electronic conduction network on the surface of the material. When synergistically doped with chlorine, the role of polyacetylene is to enhance the conductivity of the battery's positive electrode and improve the battery's performance at high rate discharge.

[0015] According to a second aspect of the present invention, a method for preparing a positive electrode material is provided, comprising: mixing and dispersing the positive electrode matrix material and the polymer coating layer material.

[0016] In some embodiments of the present invention, the method for preparing the positive electrode material further comprises spray drying the product obtained after the mixing and dispersion.

[0017] The present invention coats the surface of the positive electrode matrix material with a polymer by a spray drying method, and the coating interface not only plays the role of a protective layer, but also enhances the reaction kinetics and improves the electrical conductivity of the material. The purpose of spray drying is to convert the mixed and dispersed product into a dry particle form. Through spray drying, the polymer can be evenly coated on the surface of the positive electrode matrix material to form a protective layer, which can not only effectively protect the matrix material and prevent it from being affected by oxidation or other external factors during use, but also improve the reaction kinetics of the material and enhance its reaction speed and efficiency. At the same time, the introduction of the coating layer can also improve the electrical conductivity of the material, thereby improving the overall performance of the positive electrode material, especially in high-power, high-speed charging and discharging applications. Spray drying not only ensures the uniformity of the coating layer, but also makes the positive electrode material have better fluidity and higher activity, further improving its performance and service life in the battery.

[0018] In some embodiments of the present invention, the feed inlet temperature of the spray drying is 100-105°C, and the discharge port temperature is 80-90°C.

[0019] In some embodiments of the present invention, the mass ratio of the positive electrode matrix material to the polymer coating layer material is 50-55:1.

[0020] The role of the polymer coating at the above ratio can also improve the reaction kinetics of the material, which can effectively reduce the direct contact between the base material and the external environment and reduce adverse reactions (such as oxidation and dissolution) without excessive coating that hinders the transfer of charges.

[0021] In some embodiments of the present invention, the method for preparing the positive electrode matrix material includes: mixing and dispersing a sodium source, a potassium source, an iron source, a manganese source, a magnesium source, a phosphorus source and a reducing agent, and performing a hydrothermal reaction.

[0022] In some embodiments of the present invention, in the method for preparing the positive electrode matrix material, the pH value of the hydrothermal reaction system is 6-7.

[0023] The above pH value is conducive to obtaining a more uniform and stable particle size. The specific surface area of ​​the material is moderate, and the connection between the particles is relatively uniform, forming a complete and regular crystal structure. It will not cause instability due to excessive surface energy caused by too fine particles, nor will it affect the conductivity and high-rate performance of the battery due to too large particles.

[0024] In some embodiments of the present invention, in the method for preparing the positive electrode matrix material, the temperature of the hydrothermal reaction is 150-220°C.

[0025] In some embodiments of the present invention, in the method for preparing the positive electrode matrix material, the hydrothermal reaction time is 6 to 15 hours.

[0026] In some embodiments of the present invention, the sodium source includes at least one of sodium hydroxide, sodium carbonate, sodium bicarbonate, sodium chloride, sodium dihydrogen phosphate and sodium acetate.

[0027] In some embodiments of the present invention, the potassium source includes at least one of potassium chloride, potassium hydroxide, potassium carbonate and potassium oxide.

[0028] In some embodiments of the present invention, the iron source includes at least one of ferrous phosphate, ferrous sulfate, ferrous oxalate, ferrous oxide and ferrous hydroxide.

[0029] In some embodiments of the present invention, the manganese source includes at least one of manganese acetate, manganese carbonate, manganese dioxide, manganese oxide and trimanganese tetraoxide.

[0030] In some embodiments of the present invention, the magnesium source includes at least one of magnesium oxide, magnesium hydroxide, magnesium carbonate and magnesium sulfate.

[0031] In some embodiments of the present invention, the phosphorus source includes at least one of phosphoric acid and sodium dihydrogen phosphate.

[0032] In some embodiments of the invention, the reducing agent comprises ascorbic acid.

[0033] In some embodiments of the present invention, the method for preparing the positive electrode matrix material further comprises: washing the hydrothermal reaction product, filtering, and obtaining nano-scale sodium manganese iron pyrophosphate.

[0034] In some embodiments of the present invention, the positive electrode matrix material is doped with chlorine. Chloride ions can increase the ionic conductivity of the positive electrode material surface, stabilize the crystal structure of the material, slow down the lattice expansion and contraction of the metal oxide during the charge and discharge process, and thus improve the cycle stability and capacity retention rate. At the same time, under the above doping amount, chlorine can also react with some components in the electrolyte to slow down the occurrence of side reactions and reduce the generation of by-products, thereby improving the long-term stability of the battery.

[0035] In some embodiments of the present invention, the cathode matrix material is doped with potassium, which has a significant effect on improving the electrochemical performance of the material, especially in improving ionic conductivity, adjusting lattice structure and improving rate performance, and avoids excessive potassium from causing excessive expansion of the material structure and affecting its cycle stability.

[0036] In some embodiments of the present invention, the positive electrode matrix material is doped with magnesium. Due to its smaller ion radius (slightly larger than lithium ions and other metal ions), magnesium ions can enter the crystal structure of the positive electrode material at a certain concentration and replace a portion of the metal ion positions. Magnesium doping can effectively slow down the lattice distortion caused by volume change of the positive electrode material during the charge and discharge process.

[0037] In some embodiments of the present invention, the method for preparing the polymer coating layer material comprises: mixing the conductive polymer and iodine and then performing a solvothermal reaction.

[0038] In some embodiments of the present invention, in the method for preparing the polymer coating layer material, the solvent includes at least one of ethanol, ether, acetone, methyl pyrrolidone, chloroform, dimethylamide and benzene.

[0039] In some embodiments of the present invention, the conductive polymer and the iodine are in a ratio of 100:0.01-2 based on the amount of substances.

[0040] In some embodiments of the present invention, the temperature of the solvothermal reaction is 120-200°C.

[0041] In some embodiments of the present invention, the solvent thermal reaction time is 3 to 10 hours.

[0042] According to a third aspect of the present invention, a positive electrode sheet is provided, wherein raw materials for preparing the positive electrode sheet include the positive electrode material.

[0043] According to a fourth aspect of the present invention, a sodium ion battery is provided, wherein raw materials for preparing the sodium ion battery include the positive electrode sheet. DETAILED DESCRIPTION

[0044] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.

[0045] In the description of the present invention, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.

[0046] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.

[0047] An embodiment of the first aspect of the present invention provides a positive electrode material, comprising a positive electrode base material, and a polymer coating layer coated on a part of or the entire surface of the positive electrode base material;

[0048] The positive electrode matrix material includes Na 4-x K x Fe 3-y-z Mn y Mg z (PO 4 ) 2 P 2 O 7 Cl f , where (0≤x<0.05, 0≤y<2.2, 0.01<z<0.05, 0≤f<0.03);

[0049] The raw materials for preparing the polymer coating layer include: conductive polymer and iodine.

[0050] In combination with the first aspect, in some embodiments of the present invention, the conductive polymer includes at least one of polypyrrole, polythiophene, polyaniline and polyacetylene.

[0051] An embodiment of the second aspect of the present invention provides a method for preparing a positive electrode material.

[0052] In combination with the second aspect, in some embodiments of the present invention, a method for preparing a positive electrode material is proposed, comprising: mixing and dispersing the positive electrode matrix material and the polymer coating layer material.

[0053] In combination with the second aspect, in some embodiments of the present invention, the method for preparing the positive electrode material further includes spray drying the product obtained after the mixing and dispersion.

[0054] The present invention coats the polymer on the surface of the positive electrode matrix material by a spray drying method. The coating interface not only plays the role of a protective layer, but also enhances the reaction kinetics and improves the conductive performance of the material.

[0055] In combination with the second aspect, in some embodiments of the present invention, the feed inlet temperature of the spray drying is 100-105°C, and the discharge port temperature is 80-90°C.

[0056] In combination with the second aspect, in some embodiments of the present invention, the mass ratio of the positive electrode matrix material to the polymer coating layer material is 50-55:1.

[0057] In combination with the second aspect, in some embodiments of the present invention, the method for preparing the positive electrode matrix material includes: mixing and dispersing a sodium source, a potassium source, an iron source, a manganese source, a magnesium source, a phosphorus source and a reducing agent, and performing a hydrothermal reaction.

[0058] In combination with the second aspect, in some embodiments of the present invention, in the method for preparing the positive electrode matrix material, the pH value of the hydrothermal reaction system is 6-7.

[0059] In combination with the second aspect, in some embodiments of the present invention, in the method for preparing the positive electrode matrix material, the temperature of the hydrothermal reaction is 150-220°C.

[0060] In combination with the second aspect, in some embodiments of the present invention, in the method for preparing the positive electrode matrix material, the time of the hydrothermal reaction is 6 to 15 hours.

[0061] In combination with the second aspect, in some embodiments of the present invention, the sodium source includes at least one of sodium hydroxide, sodium carbonate, sodium bicarbonate, sodium chloride, sodium dihydrogen phosphate and sodium acetate.

[0062] In combination with the second aspect, in some embodiments of the present invention, the potassium source includes: at least one or more of potassium chloride, potassium hydroxide, potassium carbonate and potassium oxide.

[0063] In combination with the second aspect, in some embodiments of the present invention, the iron source includes at least one of ferrous phosphate, ferrous sulfate, ferrous oxalate, ferrous oxide and ferrous hydroxide.

[0064] In combination with the second aspect, in some embodiments of the present invention, the manganese source includes at least one of manganese acetate, manganese carbonate, manganese dioxide, manganese oxide and trimanganese tetraoxide.

[0065] In combination with the second aspect, in some embodiments of the present invention, the magnesium source includes at least one of magnesium oxide, magnesium hydroxide, magnesium carbonate and magnesium sulfate.

[0066] In combination with the second aspect, in some embodiments of the present invention, the phosphorus source includes at least one of phosphoric acid and sodium dihydrogen phosphate.

[0067] In conjunction with the second aspect, in some embodiments of the present invention, the reducing agent includes ascorbic acid.

[0068] In combination with the second aspect, in some embodiments of the present invention, the method for preparing the positive electrode matrix material further includes: washing the hydrothermal reaction product, filtering, and obtaining nano-scale sodium ferromanganese pyrophosphate.

[0069] In combination with the second aspect, in some embodiments of the present invention, the method for preparing the polymer coating layer material includes: mixing the conductive polymer and iodine and then performing a solvothermal reaction.

[0070] In combination with the second aspect, in some embodiments of the present invention, in the method for preparing the polymer coating material, the solvent includes: at least one of ethanol, ether, acetone, methyl pyrrolidone, chloroform, dimethylamide and benzene.

[0071] In combination with the second aspect, in some embodiments of the present invention, the conductive polymer and the iodine are in a ratio of 100:0.01-2 in terms of amount of substance.

[0072] In combination with the second aspect, in some embodiments of the present invention, the temperature of the solvothermal reaction is 120-200°C.

[0073] In combination with the second aspect, in some embodiments of the present invention, the solvent thermal reaction time is 3 to 10 hours.

[0074] An embodiment of the third aspect of the present invention provides a positive electrode sheet, and the raw materials for preparing the positive electrode sheet include the positive electrode material.

[0075] An embodiment of the fourth aspect of the present invention provides a sodium ion battery, wherein the raw materials for preparing the sodium ion battery include the positive electrode sheet.

[0076] Example 1

[0077] This embodiment provides a positive electrode material and a preparation method thereof, specifically:

[0078] S1. 21.0920g sodium carbonate, 1.1221g potassium hydroxide, 11.4950g manganese carbonate, 29.8620g iron phosphate, 0.0800g magnesium oxide, 19.7960g phosphoric acid, 0.6222g 98% hydrochloric acid, 15.9311g ascorbic acid were fixed to 150ml with deionized water, poured into a 200ml hydrothermal autoclave, reacted at 200°C for 8h, cooled naturally, washed with deionized water and filtered to obtain a nano-scale sodium manganese iron pyrophosphate material;

[0079] S2. 20 g of polythiophene and 0.02 g of iodine were dissolved in 100 ml of ethanol, poured into a 200 ml hydrothermal autoclave, reacted at 150 ° C for 5 h, cooled naturally, washed with deionized water and filtered to obtain a conductive polymer coated material;

[0080] S3. Mix 100g of sodium manganese iron pyrophosphate, 2g of conductive polymer coating material, and 100ml of deionized water, and spray granulate at a feed inlet temperature of 105°C and a discharge outlet temperature of 90°C to obtain iodine-doped polythiophene-coated sodium manganese iron pyrophosphate material.

[0081] Example 2

[0082] This embodiment provides a positive electrode material and a preparation method thereof, specifically:

[0083] S1. 47.9920g of sodium dihydrogen phosphate, 17.3000g of manganese acetate, 28.7720g of ferrous oxalate, and 14.4459g of ascorbic acid were fixed to 150ml with deionized water, poured into a 200ml hydrothermal kettle, reacted at 180°C for 8h, cooled naturally, washed with deionized water and filtered to obtain a nano-scale sodium ferromanganese pyrophosphate material;

[0084] S2. 20 g of polythiophene and 0.0200 g of iodine were dissolved in 100 ml of ethanol, poured into a 200 ml hydrothermal autoclave, reacted at 150 ° C for 5 h, cooled naturally, washed with deionized water and filtered to obtain a conductive polymer coated material;

[0085] S3. 100 g of sodium manganese iron pyrophosphate, 2 g of conductive polymer coating material, and 100 ml of deionized water were stirred evenly, and spray granulated at a feed inlet temperature of 105° C. and a discharge port temperature of 90° C. to obtain an iodine-doped polythiophene-coated sodium manganese iron pyrophosphate material.

[0086] Example 3

[0087] This embodiment provides a positive electrode material and a preparation method thereof, specifically:

[0088] S1. 33.5200g sodium bicarbonate, 0.06910g potassium carbonate, 11.4950g manganese carbonate, 30.0132g iron phosphate, 0.0583g magnesium hydroxide, 23.1202g hydrogen phosphate, 15.0062g ascorbic acid were fixed to 150ml with deionized water, poured into a 200ml hydrothermal autoclave, reacted at 180 ° C for 10h, cooled naturally, washed with deionized water, filtered and dried to obtain a nano-scale sodium manganese ferrophosphate material;

[0089] S2. 20 g of polythiophene and 0.02 g of iodine were dissolved in 100 ml of ethanol, poured into a 200 ml hydrothermal autoclave, reacted at 150 ° C for 5 h, cooled naturally, washed with deionized water and filtered to obtain a conductive polymer coated material;

[0090] S3. 100 g of sodium manganese iron pyrophosphate, 2 g of conductive polymer coating material, and 100 ml of deionized water were stirred evenly, and spray granulated at a feed inlet temperature of 105° C. and a discharge port temperature of 90° C. to obtain an iodine-doped polythiophene-coated sodium manganese iron pyrophosphate material.

[0091] Example 4

[0092] This embodiment provides a positive electrode material and a preparation method thereof. The difference between this embodiment and embodiment 1 is that polyaniline is used to replace the polythiophene in embodiment 1, and other conditions are the same.

[0093] Example 5

[0094] This embodiment provides a positive electrode material and a preparation method thereof. The difference between this embodiment and embodiment 1 is that polythiophene in embodiment 1 is replaced by polyacetylene, and other conditions are the same.

[0095] Comparative Example 1

[0096] This comparative example provides a positive electrode material and a preparation method thereof, specifically:

[0097] S1. 15.8985g sodium carbonate, 5.6105g potassium hydroxide, 11.4950g manganese carbonate, 29.8620g iron phosphate, 0.0800g magnesium oxide, 19.7960g phosphoric acid, 0.6222g 98% hydrochloric acid, 15.9311g ascorbic acid were fixed to 150ml with deionized water, poured into a 200ml hydrothermal autoclave, reacted at 200°C for 8h, cooled naturally, washed with deionized water and filtered to obtain a nano-scale sodium manganese iron pyrophosphate material;

[0098] S2. 20 g of polythiophene and 0.02 g of iodine were dissolved in 100 ml of ethanol, poured into a 200 ml hydrothermal autoclave, reacted at 150 ° C for 5 h, cooled naturally, washed with deionized water and filtered to obtain a conductive polymer coated material;

[0099] S3. 100 g of sodium manganese iron pyrophosphate, 2 g of conductive polymer coating material, and 100 ml of deionized water were stirred evenly, and spray granulated at a feed inlet temperature of 105° C. and a discharge port temperature of 90° C. to obtain an iodine-doped polythiophene-coated sodium manganese iron pyrophosphate material.

[0100] Comparative Example 2

[0101] This comparative example provides a positive electrode material and a preparation method thereof, specifically:

[0102] S1.2 1.0920g sodium carbonate, 1.1221g potassium hydroxide, 11.495g manganese carbonate, 29.8620g iron phosphate, 1.63g zinc oxide, 19.796g phosphoric acid, 0.6222g 98% hydrochloric acid, 15.9311g ascorbic acid are diluted to 150ml with deionized water, poured into a 200ml hydrothermal kettle, reacted at 200℃ for 8h, cooled naturally, washed with deionized water and filtered to obtain nano-scale sodium manganese iron pyrophosphate material;

[0103] S2. Dissolve 20g polythiophene and 0.02g iodine in 100ml ethanol, pour into a 200ml hydrothermal reactor, and react at 150℃ for 5h. After cooling naturally, wash with deionized water and filter to obtain a conductive polymer coating material;

[0104] S3. Mix 100g of sodium manganese iron pyrophosphate, 2g of conductive polymer coating material, and 100ml of deionized water, and spray granulate at a feed inlet temperature of 105°C and a discharge outlet temperature of 90°C to obtain iodine-doped polythiophene-coated sodium manganese iron pyrophosphate material.

[0105] Comparative Example 3

[0106] This comparative example provides a positive electrode material and a preparation method thereof, specifically:

[0107] S1.2 1.0920g sodium carbonate, 1.1221g potassium hydroxide, 28.7375g manganese carbonate, 7.3902g iron phosphate, 0.0800g magnesium oxide, 34.3980g phosphoric acid, 0.6222g 98% hydrochloric acid, 15.9311g ascorbic acid are diluted to 150ml with deionized water, poured into a 200ml hydrothermal kettle, and reacted at 200℃ for 8h. After natural cooling, the nano-scale sodium manganese iron pyrophosphate material is washed and filtered with deionized water;

[0108] S2. Dissolve 20g polythiophene and 0.02g iodine in 100ml ethanol, pour into a 200ml hydrothermal reactor, and react at 150℃ for 5h. After cooling naturally, wash with deionized water and filter to obtain a conductive polymer coating material;

[0109] S3. Mix 100g of sodium manganese iron pyrophosphate, 2g of conductive polymer coating material, and 100ml of deionized water, and spray granulate at a feed inlet temperature of 105°C and a discharge outlet temperature of 90°C to obtain iodine-doped polythiophene-coated sodium manganese iron pyrophosphate material.

[0110] Comparative Example 4

[0111] This comparative example provides a positive electrode material and a preparation method thereof, specifically:

[0112] S1. Add 21.0920g sodium carbonate, 1.1221g potassium hydroxide, 11.4950g manganese carbonate, 29.8620g iron phosphate, 0.0800g magnesium oxide, 19.7960g phosphoric acid, 0.6222g 98% hydrochloric acid, and 15.9311g ascorbic acid to 150ml with deionized water, pour into a 200ml hydrothermal kettle, and react at 200℃ for 8h. After cooling naturally, wash with deionized water and filter to obtain nano-scale sodium manganese iron pyrophosphate material;

[0113] S2. Mix 100g of sodium manganese ferric pyrophosphate, 2g of polythiophene and 100ml of deionized water and spray granulate at a feed inlet temperature of 105°C and a discharge outlet temperature of 90°C to obtain a polythiophene-coated sodium manganese ferric pyrophosphate material.

[0114] Test example

[0115] A1. Weigh the sodium manganese iron pyrophosphate material, conductive agent, and binder in the embodiment and the comparative example according to the mass ratio: the mass ratio of the above four substances is: 8:1:1; wherein the conductive agent is conductive carbon black; the binder is PVDF;

[0116] A2. Weigh 100g NMP and add it into the blue-capped bottle;

[0117] A3, Preparation of glue: Add 3g of binder to the NMP in step 2, put in a rotor, and stir with a magnetic stirrer for 10h until the binder is completely dissolved;

[0118] A4. Preparation of conductive adhesive: weigh 3.3334 g of the adhesive solution in step 3 into a 5 ml pulping bottle, weigh 0.1000 g of conductive agent and add it to the pulping bottle, and stir with a magnetic stirrer for 30 min until the conductive agent is evenly dispersed;

[0119] A5. Preparation of slurry: Weigh 0.8000 g of positive electrode material into the slurry preparation bottle in step 4, stir slowly for 30 min with a magnetic stirrer until the positive electrode material is completely wetted, and stir quickly for 4 h until the positive electrode material is evenly dispersed; obtain a positive electrode slurry with a solid content of 23.6%;

[0120] A6. Use a preparation device to coat the slurry in step 5 on aluminum foil with a coating thickness of 150um; put the electrode into a hot air drying oven and dry it at 105°C for 1h;

[0121] A7. Roll the pole piece dried in step 6, and the pole piece compaction density is 2.1g / cm3;

[0122] A8, cutting the rolled electrode sheet in step 7 into a 14 mm diameter electrode sheet, thus obtaining a positive electrode sheet;

[0123] Using the sodium sheet as the counter electrode, the positive electrode sheet obtained in the embodiment and the comparative example and the sodium sheet were used to make a 2032 button battery in a glove box;

[0124] Cycle life test method: The prepared battery is charged and discharged at 25°C, 2-4.3V voltage range, 0.2C small current to obtain 0.2C first charge and first discharge, first efficiency = first discharge / first charge*100%. 1C current charge and discharge cycle test, cycle 1000 times, record the 1000th and 1st battery discharge capacities, and calculate the discharge retention rate. Discharge retention rate = 1000th discharge capacity / 1st discharge capacity*100%.

[0125] Rate performance test method: charge and discharge at 2C high current at 25℃, 2-4.3V voltage range, and calculate the 2C / 0.2C rate value. The same method can be used to calculate the 5C / 0.2C rate value.

[0126] The properties of the embodiments and comparative examples are shown in Table 1.

[0127] Table 1 Performance results

[0128]

[0129] The element ratio of Comparative Example 1 and Comparative Example 3 is deviated from Na 4-x K x Fe 3-y-z Mn y Mg z (PO 4 ) 2 P 2 O 7 Cl f, where the ratio in the range of (0≤x<0.05, 0≤y<2.2, 0.01<z<0.05, 0≤f<0.03) leads to a decrease in the electrical properties of the material. Excessive potassium will reduce the content of active element sodium ions, resulting in a decrease in capacity; excessive manganese will cause changes in the structure and properties of the positive electrode material, forming a poor crystal structure, and the poor conductivity of manganese will increase the internal resistance of the battery, reduce the insertion and extraction rate of sodium ions, and reduce the capacity and cycle life of the battery. In Comparative Example 2, zinc oxide replaces magnesium oxide, and the electrical properties of the material are reduced. The resistivity of zinc is 51.96mΩ.m, and the resistivity of magnesium is 44.5mΩ.m, that is, the conductivity of zinc is lower, and the conductivity of zinc-doped materials is lower than that of magnesium-doped materials. In addition, magnesium doping enhances the structural stability of the material, which can further improve the conductivity of the material. Comparative Example 4 is to use an undoped conductive polymer to coat the sodium manganese iron pyrophosphate positive electrode matrix material. The basic conditions for the conductivity of the material are: the free flow and flow channel of electrons. The conductive polymer main chain contains alternating single and double bonds, a large conjugated π system is formed, and there is an electron flow channel. Without the doping of iodine, there is a lack of driving force for the free flow of electrons, that is, the conductive properties of the conductive polymer cannot be normally exerted. In addition, the complex framework structure of sodium manganese ferric pyrophosphate phosphate itself limits the free movement of electrons. The band gap width of sodium manganese ferric pyrophosphate phosphate is large, which also affects the conductivity of the material. Therefore, when the conductive properties of the material are poor, the electrical properties of the material cannot be normally exerted.

[0130] The above is a detailed description of the embodiments of the present invention, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

Claims

1. A sodium manganese iron pyrophosphate positive electrode material, characterized in that It comprises a positive electrode base material, and a polymer coating layer coated on a part of the surface or the entire surface of the positive electrode base material; The positive electrode matrix material includes Na 4-x K x Fe 3-y-z Mn y Mg z (PO4)2P2O7Cl f , where (0≤x<0.05, 0≤y<2.2, 0.01<z<0.05, 0≤f<0.03); The raw materials for preparing the polymer coating layer include: conductive polymer and iodine.

2. The sodium ferromanganese pyrophosphate positive electrode material according to claim 1, characterized in that The conductive polymer includes at least one of polypyrrole, polythiophene, polyaniline and polyacetylene.

3. A method for preparing the sodium ferromanganese pyrophosphate positive electrode material as claimed in claim 1 or 2, characterized in that: include: The positive electrode base material and the polymer coating layer material are mixed and dispersed.

4. The method for preparing the sodium ferromanganese pyrophosphate positive electrode material according to claim 3, characterized in that: The mass ratio of the positive electrode matrix material to the polymer coating layer material is 50-55:

1.

5. The method for preparing the sodium ferromanganese pyrophosphate positive electrode material according to claim 3, characterized in that: The preparation method of the positive electrode matrix material comprises: A sodium source, a potassium source, an iron source, a manganese source, a magnesium source, a phosphorus source and a reducing agent are mixed and dispersed to carry out a hydrothermal reaction.

6. The method for preparing the sodium ferromanganese pyrophosphate positive electrode material according to claim 3, characterized in that: The preparation method of the polymer coating layer material comprises: mixing a conductive polymer and iodine and then performing a solvent thermal reaction.

7. The method for preparing the sodium ferromanganese pyrophosphate positive electrode material according to claim 6, characterized in that: Calculated by amount, the conductive polymer and the iodine are in a ratio of 100:0.01-2.

8. The method for preparing the sodium ferromanganese pyrophosphate positive electrode material according to claim 7, characterized in that: The temperature of the solvent thermal reaction is 120-200°C.

9. A positive electrode sheet, characterized in that: The raw materials for preparing the positive electrode sheet include the positive electrode material.

10. A sodium ion battery, characterized in that: The raw materials for preparing the sodium ion battery include the positive electrode sheet according to claim 9.

Citation Information

Patent Citations

  • Positive electrode active material, preparation method thereof, positive electrode plate, battery and electric equipment

    CN117038973A

  • Sodium ion battery polyanion positive electrode material and preparation method thereof

    CN117525391A

  • Polyanionic sodium ion battery positive electrode material, preparation method thereof and sodium ion battery

    CN118213494A

  • In-situ polymerization coated ferric sodium phosphate pyrophosphate composite material as well as preparation method and application thereof

    CN119008877A

  • Reversible electrochemical doping of conjugated polymers and secondary batteries based thereon

    US4728589A